Reasons for Performance Differences among ISO 9001:2015-Certified Construction Companies in the Perspective of TQM Elements - Okudan, Ozan; Budayan, Cenk (ASCE-AMER SOC CIVIL ENGINEERS, 2021)
Although some studies identified positive effects of ISO certification on company performance, some studies proposed that the ISO 9000 certification does not guarantee high performance. To understand the reasons for performance differences between ISO-certified companies, these two assessments should be examined. In this way, ISO-certified companies can use the certification to improve their performance. Integrating both ISO 9000 certification and total quality management (TQM) is considered a vital factor for increasing the company performance. Therefore, TQM can be a crucial complement to ISO certification. One reason for the performance difference among ISO-certified companies may stem from ISO 9000-certified companies' following the ISO 9000 standards and applying TQM elements concurrently, which improves the performance, whereas other companies still rely solely on ISO 9000. However, this strategy does not provide the expected improvements to achieve high performance. This study investigated the reasons for performance variances among ISO 9000-certified companies by considering TQM elements. Forty TQM elements and eight performance metrics were extracted by conducting a literature survey, questionnaire survey, and focus group discussions. Another questionnaire survey was conducted among 65 participants from ISO 9000-certified construction companies. The data were examined by performing a cluster analysis and ANOVA. The analysis revealed that ISO-certified companies should not rely solely on the ISO certification. They should integrate ISO certification and TQM to increase their organizational and operational performance. Furthermore, these companies have deficiencies in encouraging employees to learn how to improve skills. They fall short in developing an environment for on-the-job training, quality data to evaluate supervisors and managers, and quality data to manage quality.
Keywords: ISO 9000 certification; Total quality management; Performance; Construction industry; MEASURING ORGANIZATIONAL PERFORMANCE; CRITICAL SUCCESS FACTORS; FINANCIAL PERFORMANCE; ISO-9000 CERTIFICATION; BUSINESS PERFORMANCE; FIRM PERFORMANCE; IMPACT; IMPLEMENTATION; INNOVATION; Engineering